Women accessing high-value niche markets in Jamaica - Rowan-Campbell, Dorienne (Technical Centre for Agricultural and Rural Cooperation, 2019)
Dorienne Rowan-Campbell shares her experience as an organic farmer, who got into this activity by passion, and how she is influencing other women to get into organic farming in Jamaica.